PERBEDAAN KADAR GLUKOSA MENGGUNAAN DARAH DENGAN ANTIKOAGULAN DAN TANPA ANTIKOAGULAN METODE POCT - NORMA FARIZAH FAHMI; Nailufar Firdaus; Siti Rohmah B (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2020)
The blood glucose can be said to be abnormal if lees or surpassing the reference value. According to the town kendari ismoyo clinic, the number of blood glucoseexaminations are common among blood chemistry checks. The purpose this study is to determine the levelsof blood glucose by giving anticoagulants and without anticoagulants. This research used shaphiro wilk independent variables was an anticoagic while the dependent variable was a blood glucose level of a Pregnant woman TM I.Population as many as 53 Pregnant Woman. As for the samples as many as 16 college students. The research was carried out in the clinical laboratory of the STIKes Ngudia Husada Madura on July 3, 2019. A tehnik sampel used was simple randem sampling data collection of blood glucose levels used the parametric scale of POCT methods the data analysis was based on wilcoxxon 0,05. Result investigation showed that at an average score blood glucose levels used anticoagulant was (62,5%) as for value average blood glucose level whitout used the anticoagulant was (56,2%). Analysis results available from results p value (0,012) < α (0,05), so it can be on deduce there was a difference in glucose with the use of anticoagulant and with no anticoagulant.